2009
DOI: 10.1130/g25640a.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic subsidence on relative sea-level rise in the Fraser River delta

Abstract: Subsidence is a common cause of amplifi ed relative sea-level rise, fl ooding, and erosion in coastal environments. In particular, subsidence due to sediment consolidation can play a signifi cant role in relative sea-level rise in large deltas. We use a combination of InSAR (interferometric synthetic aperture radar), leveling, and global positioning system data to map absolute vertical land motion in the Fraser River delta, western Canada. We show that primary consolidation of shallow Holocene sediments is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 19 publications
3
69
1
1
Order By: Relevance
“…4e). These CR values are in the range of what it is observed for modern deltas: 1-2 mm yr −1 for the Fraser, Nile and Mississippi deltas (Mazzotti et al, 2009;Wöppelmann et al, 2013;Törnqvist et al, 2008) and up to 15-18 mm yr −1 in some parts of the Po and Ganges-Brahmaputra deltas (Teatini et al, 2011;Higgins et al, 2014). Contrary to those studies (except for the Po delta that seems to behave similarly), the CR increases until the coastline.…”
Section: Deltas and Sediment Compactioncontrasting
confidence: 76%
See 2 more Smart Citations
“…4e). These CR values are in the range of what it is observed for modern deltas: 1-2 mm yr −1 for the Fraser, Nile and Mississippi deltas (Mazzotti et al, 2009;Wöppelmann et al, 2013;Törnqvist et al, 2008) and up to 15-18 mm yr −1 in some parts of the Po and Ganges-Brahmaputra deltas (Teatini et al, 2011;Higgins et al, 2014). Contrary to those studies (except for the Po delta that seems to behave similarly), the CR increases until the coastline.…”
Section: Deltas and Sediment Compactioncontrasting
confidence: 76%
“…Since the temporal decrease of subsidence rate typically follows an exponential curve with a relatively short time constant (likely shorter than 100 years) (Terzaghi and Peck, 1967), it seems unlikely that compaction of the basal Pleistocene strata could explain the 4-10 mm yr −1 of compaction rate (CR) observed at the surface. We thus conclude that the subsidence is mainly related to the compaction of the Holocene wedge as inferred for other deltas such as the Po, Mississippi, Fraser or GangesBrahmaputra deltas (Mazzotti et al, 2009;Törnqvist et al, 2008;Teatini et al, 2011;Higgins et al, 2014, e.g.). Moreover, InSAR data show here an increase of the subsidence rate from inland to the coastline that correlates well with the increase of the Holocene sediment thickness.…”
Section: Deltas and Sediment Compactionsupporting
confidence: 70%
See 1 more Smart Citation
“…It suggests that other factors like sediment consolidation and loading may also contribute to the total subsidence in this part of the Yellow River delta. These subsidence rates will decrease through time if they are caused by loading [16].…”
Section: Subsidence Patterns In Gudao Town (Oilfield) Gudong Oilfielmentioning
confidence: 99%
“…For river delta studies, InSAR has previously been used to measure subsidence due to sediment consolidation and artificial loading in several deltas, including the Pearl River [14], Nile [15] and Fraser River [16] deltas. In the Yellow River delta, Higgins et al [9] showed subsidence rates as high as 250 mm/yr from InSAR.…”
Section: Introductionmentioning
confidence: 99%